Weird : the power of being an outsider in an insider world - Khazan, Olga, 1986- (Hachette Go, an imprint of Hachette Books, 2020)
Explores why it is that we crave conformity, how that affects people who are different, and what they can do about it. Dives into the history of social norms and why some people hew to them more strictly than others, explores the causes behind-and the consequences of-social rejection, reveals the hidden upsides to being "weird," as well as the strategies that people who are different might use in order to achieve success in a society that values normalcy, and follows the trajectories of unique individuals who either decided to be among others just like them; to stay weird; or to dwell somewhere in between.